(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study evaluates the influence of parity on the clinical characteristics of the climacteric period in women. The climacteric period involves progressive ovarian hormonal decline, leading to vasomotor, urogenital, metabolic, skeletal, and psychological manifestations. Reproductive history, particularly parity, may modify the severity and timing of these symptoms through hormonal, metabolic, and end-organ adaptations. The study analyzes clinical features among nulliparous and multiparous women based on literature synthesis and cohort data. Findings indicate that multiparous women tend to have later onset of menopause, milder vasomotor and psychological symptoms, and more stable bone health, whereas they are at higher risk for pelvic floor and urogenital disorders. Nulliparous women show earlier ovarian decline, higher vasomotor and psychological symptom burden, and increased metabolic risk. An integrative approach considering parity allows for targeted preventive care and individualized clinical management during the climacteric transition.